Effect of Plant Density on Physico-chemical Properties of Soils and Growth of Teak - Pagar, P.C.; Gabhane, V.V.; Khobragade, Nitu (Indian Journal of Agroforestry, 2020)
An experiment was carried out on shallow to moderately deep, clay to clay loam textured soils at Futala- farm, College of Agriculture, Nagpur to Study the effect of Teak (Tectona grandis) in Agroforestry system with five spacings in plantations on physico-chemical properties of soil. The soil properties like bulk density, pH, and free lime increased with depth while EC, organic carbon, CEC, exchangeable bases decreased with depth. In all the spacings and plantation bulk density and pH of the soil decreased while organic carbon content improved. The percentage improvement in these soil properties is more in narrow spacing as compared to wider spacing.